Applicability of RAMS for a simulation to provide inputs to an air quality model: Modeling evaluation and sensitivity test - Chatchawan Vongmahadlek (2018)
In this study, the Regional Atmospheric Modeling System (RAMS) is applied to simulate historical wind and temperature fields in the Bang Pakong area of Thailand in order to support a photochemical air quality modeling system in summer and winter time. We use high-resolution datasets of Digital Elevation Model (DEM), global monthly Sea Surface Temperature (SST), and global reanalysis data as a part of the global analysis information for a preparation of geo-terrestrial processes. The studied domain covers the Central and Eastern regions of Thailand. The based model setup includes one-way with the nesting grid of the Bang Pakong area using typical modeling parameters. The configurations of each domain (i.e., time steps and grid resolution) are formulated by grid specifications. The results indicate that RAMS can be applied to the historical meteorology (i.e., wind and temperature fields) over the complex terrain and the coast area. The statistical evaluation is applied in an average basis of the ground surface and found acceptable agreement between available observed and simulated results. Data assimilation by nudging analysis is applied to Thailand's weather information obtained from the Thai Meteorological Department (TMD) to improve modeling simulations. This technique shows the better improvement of modeling performance. Sensitivity tests on some physical parameters and schemes (i.e., convective cumulus and radiation parameters) are conducted to investigate their influence on modeling responses. The modeling performance of physical parameters to the area of study are discussed.